2014
DOI: 10.1186/2052-336x-12-23
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective approach to assess human health risks associated with growing air pollution in urbanized area of Thar Desert, western Rajasthan, India

Abstract: Air pollution has been a matter of great concern globally because of the associated health risks to individuals. The situation is getting worse in developing countries with more urbanization, industrialization and more importantly the rapidly growing population posing a threat to human life in the form of pulmonary, cardiovascular, carcinogenic or asthmatic diseases by accumulating toxic pollutants, harmful gases, metals, hydrocarbons etc.ObjectiveThe present study was undertaken to assess the magnitude of amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Similarly, a study investigating SO 2 -and PM-induced air pollution and the admissions of asthma and COPD patients to the emergency unit showed that high SO 2 values were found to be associated with admission to the emergency unit [27]. A study by Rumana et al [28] examined the relationship between the levels of PM2.5, PM10, nitrogen oxides (NOx), SO 2 , ammonia (NH 3 ), and ozone (O 3 ), urbanization, and air pollution and emergent respiratory and cardiac diseases and revealed that respiratory infections (25%) and the prevalence of asthma/COPD (4%) were associated with increased air pollution. In literature, studies have demonstrated a linear relationship between air pollution and respiratory tract diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study investigating SO 2 -and PM-induced air pollution and the admissions of asthma and COPD patients to the emergency unit showed that high SO 2 values were found to be associated with admission to the emergency unit [27]. A study by Rumana et al [28] examined the relationship between the levels of PM2.5, PM10, nitrogen oxides (NOx), SO 2 , ammonia (NH 3 ), and ozone (O 3 ), urbanization, and air pollution and emergent respiratory and cardiac diseases and revealed that respiratory infections (25%) and the prevalence of asthma/COPD (4%) were associated with increased air pollution. In literature, studies have demonstrated a linear relationship between air pollution and respiratory tract diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The sources of pollution vary from small unit of cigarettes and natural sources such as volcanic activities to large volume of emission from motor engines of automobiles and industrial activities. [12] Long-term effects of air pollution on the onset of diseases such as respiratory infections and inflammations, cardiovascular dysfunctions, and cancer is widely accepted;[3456] hence, air pollution is linked with millions of death globally each year. [789] A recent study has revealed the association between male infertility and air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur dioxide (SO 2 ) is one of the most toxic gases in air-polluted areas [63,64] . It is commonly released in the atmosphere from fossil fuel combustion [65] .…”
Section: Sulfur Dioxidementioning
confidence: 99%